Pentecostal Christianity and Stewardship of Environmental Security in Southwestern Nigeria - Emmanuel Olusegun Lana; Emmanuel Adebayo Popoola (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Threats to environmental security abound in southwestern Nigeria. Pentecostal churches, with their large following and pervasive influence could promote environmental stewardship geared towards mitigating this problem. It is against this backdrop that this study investigated the role of Pentecostal Christianity in southwestern Nigeria in ensuring environmental security.Objective: The aim of the paper is to examine the extent to which Pentecostal Christian beliefs and teachings address environmental issues. The paper further explores the role of Pentecostal churches in promoting environmental stewardship through their programmes and activities.Methods: Using a survey research design, data was obtained from 150 members using the Questionnaire on Pentecostal Christianity and Stewardship of Environmental Security (QPECASES, r = .78). The study was guided by four research questions. Data was analyzed using descriptive statistics particularly frequency count, mean and standard deviation.Result: Results show a considerable belief-practice discrepancy. Significant obstacles still exist, such as unmet negative effects from church activities (Mean=3.08) and an ideological emphasis on evangelism (Mean=2.85), even though respondents confirmed that teachings handle environmental issues to a high degree (Weighted Mean=3.15). Churches regularly arrange environmental projects (Mean=3.72), and leadership modeling can help (Mean=2.99).Conclusion: According to the study's goals, Pentecostal Christianity provides powerful theological resources to encourage environmental stewardship, but this hasn't yet been properly translated into regular practice. Therefore, Pentecostal churches must undergo institutional transformation as well as theological reorientation in order to address environmental security. In particular, creating official green church policies and incorporating environmental stewardship into congregational teaching and discipleship programs are crucial tactics for coordinating Pentecostal beliefs, church operations, and environmental responsibility in southwestern Nigeria.